2017
DOI: 10.2135/cropsci2017.02.0074
|View full text |Cite
|
Sign up to set email alerts
|

Zoysiagrass (Zoysiaspp.) History, Utilization, and Improvement in the United States: A Review

Abstract: Z oysiagrass (Zoysia 1 spp. Willd. 2) is an introduced, perennial, sod-forming species in the United States that is well adapted for use as a turf in the transitional and warm climatic regions and requires minimal maintenance inputs. Three 3 primary species of zoysiagrass [Zoysia japonica Steud. 4 , Zoysia matrella (L. 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 123 publications
1
98
1
1
Order By: Relevance
“…These intraspecies differences highlight the impact of the high genetic diversity within Zoysia spp. that might be responsible for differences in herbicide sensitivity across zoysiagrass cultivars (Lewis et al, 2010; Patton et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These intraspecies differences highlight the impact of the high genetic diversity within Zoysia spp. that might be responsible for differences in herbicide sensitivity across zoysiagrass cultivars (Lewis et al, 2010; Patton et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…Zoysiagrass exhibits more shade and winterkill tolerance than bermudagrass ( Cynodon spp. ), fewer disease and insect problems than St. Augustinegrass [ Stenotaphrum secundatum (Walter) Kuntze], and moderate salinity tolerance and wear tolerance compared with other warm‐season grasses (Patton, 2010; Patton et al, 2017a). The most troublesome weeds in zoysiagrass turf are frequently other warm‐season grasses with a similar growth habit and growing season.…”
mentioning
confidence: 99%
“…McCauley et al (2019) reported that hybrid bermudagrass could completely recover in 42 d when fraise-mown in mid-May and 28 d when fraise-mown in mid-June in North Carolina, which is quicker than this report of zoysiagrass recovery from fraise mowing on June 6th in Tennessee. Zoysiagrass is known to both establish more slowly than other species and to recover slowly from injury (Patton et al 2017). Particularly, the cultivar 'Meyer' tested in this experiment is known to establish and recuperate slowly.…”
Section: Annual Bluegrass Reductionmentioning
confidence: 96%
“…It is important to mention that cv. Emerald, released in the USA in 1955 (Patton et al, 2017), is a cross between Zoysia japonica and Zoysia pacifica, whereas cv. 'Esmeralda TM ', produced in Brazil, is Zoysia japonica.…”
Section: History Of Sod Production In Brazilmentioning
confidence: 99%